The effect of blood glucose and lipid risk factors on idiopathic sudden sensorineural hearing loss: A two-sample Mendelian randomization study - Bang-yu Deng; Yun-xia Zhao; Ji-sheng Liu (Brazilian Journal of Otorhinolaryngology)
Objective: To delve into the potential associations of blood glucose and lipid parameters with Sensorineural Hearing Loss (SHL) and Idiopathic Sudden Hearing Loss (ISHL) through a bidirectional two-sample Mendelian Randomization (MR) analysis, providing insights into the metabolic contributions to hearing loss. Methods: Genome-Wide Association Studies (GWAS) database from European populations were analyzed to assess the causal effects of blood glucose and lipid risk factors on SHL and ISHL. Single Nucleotide Polymorphisms (SNPs) meeting strict p-value thresholds were used as instrumental variables. MR methods, including Inverse Variance-Weighted (IVW), MR-Egger, and weighted median, were employed. Heterogeneity and pleiotropy were evaluated using Cochran’s Q and MR-Egger intercept. Reverse MR analysis assessed the potential impact of SHL and ISHL on metabolic factors. Results: Triglycerides (TG) exhibited a significant causal effect on SHL (OR = 1.162, 95% CI 1.072–1.260, p < 0.01), with findings consistent across MR methods. No other metabolic factors exhibited significant causal effects on SHL. Similarly, no associations were found between any metabolic factors and ISHL. Reverse MR analysis revealed that ISHL may causally influence fasting glucose (OR = 1.001, 95% CI 1.001–1.013, p < 0.01) and T2DM (OR = 1.039, 95% CI 1.029–1.049, p < 0.01), but SHL showed no significant reverse effects. Conclusion: TG is a causal risk factor for SHL, whereas ISHL may influence glucose metabolism. These findings underscore the metabolic distinctions between SHL and ISHL and their respective etiologies. Level of evidence: Level 2.